IL-13 Genetic Susceptibility to Bullous Pemphigoid: A Potential Target for Treatment and a Prognostic Marker - Wang, Yiman; Mao, Xuming; Liu, Yangchun; Yang, Yuyan; Jin, Hongzhong; Li, Li (Frontiers in Immunology, 2022)
Background Bullous pemphigoid (BP) is a senile chronic autoimmune bullous skin disease with a high relapse rate, which significantly impairs patients’ quality of life and contributes to disease mortality. This observational case-control study explores the gene polymorphisms of cytokines and their clinical significance in Chinese patients with BP. Methods IL-1α (rs1800587), IL-1β (rs16944, rs1143627, rs1143634), IL-4 (rs2243250), IL-6 (rs1800795), IL-10 (rs1800896, rs1800871, rs1800872), IL-13 (rs1800925, rs20541), TNF-α (rs1799964, rs1800630, rs1799724, rs361525), IFN-γ (rs1799964, rs1800630, rs361525, rs1800629, rs4248160, rs1800750), and TGF-β1 (rs2317130, rs1800469, rs4803457) genes were genotyped in the healthy controls and BP patients, respectively. Expression of these cytokines in serum was measured. Medical profiles of patients, including baseline characteristics and prognosis, were statistically analyzed. Results We found that IL-1 β and IL-13 concentrations were higher in the BP patients’ sera compared to those in the controls. For IL-13, significant differences were found in the nucleotide ratio/genotype/haploid frequency/haplotype, respectively. IL-13 (rs20541, rs1800925) is related to gender, and the IL-13 genotype was significantly associated with recurrence. Conclusions BP is associated with IL-13 gene polymorphism and IL-13 concentration is elevated in blood circulation in patients with BP. Our results support that IL-13 is relevant in the pathogenesis of BP, suggesting that IL-13 could potentially represent a promising target for BP therapy and a prognostic marker.